Exposure to Bisphenol A Affects Lipid Metabolism in Drosophila melanogaster. (11th December 2013) - Williams, Michael J.; Wang, Yi; Klockars, Anica; Monica Lind, P.; Fredriksson, Robert; Schiöth, Helgi B.
Abstract Exposure to bisphenol A (BPA) in rodents was shown to induce obesity, yet the mechanism by which BPA might induce obesity is still unclear. We employed the genetically tractable model organism, Drosophila melanogaster, to test the effects of raising them on food containing various concentrations of BPA. Of note, raising males on food containing BPA were susceptible to starvation, possibly by inhibiting their ability to perform lipolysis during starvation, leading to significantly increased lipid content after 24 hr of fasting. Furthermore, feeding males with BPA significantly inhibited the expression of insulin‐like peptides. From these results, we conclude that BPA may inhibit lipid recruitment during starvation in Drosophila.